The origins of major platelet receptor nomenclature. (2nd January 2017) - Clemetson, Kenneth J.
Abstract: The nomenclature of the major platelet receptors may appear complex, but in fact there are logical reasons why it developed in the way it did. In this short review, I describe the origins of this nomenclature, how it developed as more information became available and as relationships were established with receptors on other types of cells. Difficulties have also arisen with alternative nomenclature systems and the various equivalences with these are described and listed. There remain areas such as immunology and transfusion where the accepted nomenclature leaves something to be desired, but it is unlikely that major changes will occur.